The Role of Extracellular Vesicles Secreted From Thermal Stress-Induced Adipose-Derived Stem Cells on Bone Regeneration - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Purpose: Extracellular vesicles (EVs) are responsible for intercellular communication. Mesenchymal stem cell-derived vesicles have been shown to have similar properties as functional mesenchymal stem cells. The aim of this study was to compare the therapeutic benefit of EVs obtained from adipose tissue-derived stem cells (ADSC) on bone repair whereas using ss-tricalcium phosphate (ss-TCP) biomaterial as a carrier. Materials and Method: A single critical size bone defect of 8 mm in diameter was created on the right side of rat calvarium using a custom-made punch needle. Animals were randomly divided into 5 groups: group 1 (no treatment), group 2 (bone graft), group 3 (ss-TCP + ADSC), group 4 (ss-TCP + EV), group 5 (ss-TCP). Eight weeks later, animals were sacrificed and histologic and radiologic evaluation was performed. Results: Semiquantitative histologic scoring demonstrated significantly higher bone regeneration scores for groups 2, 3, and 4 compared to group 1. Radiologic imaging showed significantly higher bone mineral density for groups 2, 3, and 5 compared to group 1. There were no significant differences between treatment groups in either histologic or radiologic scoring. Conclusions: Our data showed that EVs provided from thermally induced ADSCs did not show any significant difference in bone regeneration when compared to ADSCs themselves. Future studies should focus on determining the optimum amount and content of EV application since these vary significantly depending on the microenvironment.
Keywords: Adipose-derived stem cell; bone regeneration; extracellular vesicle; BETA-TRICALCIUM PHOSPHATE; EXOSOME-MEDIATED TRANSFER; IN-VITRO; DIFFERENTIATION; TRANSDIFFERENTIATION; ANGIOGENESIS; OSTEOGENESIS; PROGENITORS; PROTEINS; DEFECTS